Foto Esai Sepak Bola di Museum Olahraga Nasional: Nostalgia dan Komunitas Terbayang - Deddy Setiawan; Tisna Prabasmoro; Widyo Nugrahanto (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
People engage in nostalgia through museums and their experiences, but little study has been done to link the three. The article places photo essays at the National Sports Museum as a trigger for visitors' memories of events in photos related to self-identity and the nation. It explains the projection of collective identity when the visitors revisit their old memories while consuming the event documentation in the photo essays, and places the photo essays as a medium for imagined community nostalgia. The article argues that the photo essays not only help restore visitors' memories and knowledge but also build personal and collective identities that foster a sense of belonging and inclusion.